Inflation persistence in central and eastern European countries - Zsolt Darvas; Balázs Varga (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
This article studies inflation persistence with time-varying coefficient autoregressions for twelve central European countries, in comparison with the United States and the euro area. Inflation persistence tends to be higher in times of high inflation. Since the oil price shocks, inflation persistence has declined both in the US and the euro-area. In most central and eastern European countries, for which our study covers 1993-2012, inflation persistence has also declined, with the main exceptions of the Czech Republic, Slovakia and Slovenia, where persistence seems to be rather stable. These findings have implications for the conduct of monetary policy and for a possible membership in the euro area. We also conclude that the OLS estimate of an autoregression is likely upward biased relative to the time-average of time-varying parameters, when the parameters change.
Keywords: C22; E31; 330; flexible least squares; inflation persistence; Kalman-filter; time-varying coefficient models